The Positive Skin Prick Test not Correlate with Disease Severity and Quality of Life in Atopic Dermatitis Patients - Oki Suwarsa; Erfina Rohana Sormin; Endang Sutedja; Hartati Purbo Dharmaji (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Atopic dermatitis (AD) is a skin disease which cause stress to the patients. The chronic process of AD can cause physical, social, and psychological impairments. The severity of AD can also be affected by allergen exposures, which in turn will affect the quality of life of the patient. Skin prick test (SPT) can be used to evaluate allergen sensitization. Purpose: To evaluate correlation between SPT positivity to severity and quality of life of AD patients. Methods: The study was an observational cross-sectional study. Twenty five AD patients were recruited based on inclusion and exclusion criteria. Questionnaire was used to measure the quality of life of patients, and Scoring of Atopic Dermatitis (SCORAD) to measure the disease severity. Most of participants were women (80%), with median of age 26.84±13.71. Results: Positive SPT was obtained in 68% of patients, most of them were caused by house dust mites (55.2%). Seventy six percent of patients experienced mild AD, 12% moderate AD, and also 12% patients experienced severe AD. Significant correlation was observed between the severity and quality of life (p=0.001;r=0.617), while the SPT positivity has no correlation with the severity (p=0.912;r=-0.023) and quality of life (p=0.959;r=0.011). Conclusion: This study revealed that the severity of the disease has a correlation with quality of life, but SPT positivity has no significant correlation with severity and quality of life.